Surface-enhanced coherent anti-Stokes Raman scattering based on coupled nanohole–slit arrays. Issue 22 (27th May 2022) - Feng, Yanting; Wang, Yu; Shao, Fenglan; Meng, Lingyan; Sun, Mengtao
Abstract : LSPR and SPP modes of the nanohole–slit array are simultaneously utilized to enhance pump, Stokes and anti-Stokes fields for the highest SECARS EF. Abstract : Metal nanohole arrays show excellent performance when applied for sensing, optical fibers, and surface-enhanced spectroscopy, but they are not ideal candidates for surface-enhanced coherent anti-Stokes Raman scattering (SECARS) because of their low enhancement factor (EF). Here, the finite element method was used to study the dependence of the period, width, and thickness of nanoslits on the EF of SECARS and optical transmission in Au nanohole–slit arrays. Nanoslits across the nanoholes significantly modulated the SECARS signal, and we observed an ∼10 6 improvement in the EF of SECARS compared with the nanohole-only structure. Uniform and stable 2D hotspots at the open surface of plasmonic nanohole–slit structures provided a huge SECARS EF as high as 18 orders of magnitude. Directional SECARS emission revealed strong forward and backscattering with high directionality, showing a smaller divergence angle of 14° on the reflective side of the nanohole–slit array. These results provide a fundamental understanding of SECARS in coupled nanohole–slit arrays and are useful for designing a SECARS platform with high sensitivity.